Full Print-Ready Version of Kinerja: Jurnal Bisnis dan Ekonomi - JURNAL KINERJA (KINERJA, 2016)
Dear AuthorsThis is a print ready version of KINERJA: Jurnal Bisnis dan Ekonomi.Please use it during waiting process of printed version available to spread. Best Regards, Editor in Chief